Effects of neomycin on absorption, synthesis, and/or flux of cholesterol in man. - Sedaghat, A (1975)
The mode of action of the hypocholesteremic drug neomycin (2 g/day) was studied in four patients. All showed a significant reduction in plasma cholesterol concentrations (mean 25 percent, range 18-31 percent), and in one of three patients with hyperglyceridemia there was a decrease of plasma triglycerides of 26 percent. Cholesterol absorption was measured in three of four patients: there was a marked decrease. Sterol balance studies in four patients showed an unabating increase in fecal neutral steroid excretion (mean increase 345 mg/day, range 323-361) for 3-5 wk after plasma cholesterol levels had reached a new and lower plateau. Fecal acidic steroid excretion increased temporarily in two patients, with a sustained increase of 93 mg/day in only one. Daily stool weights increased significantly in three of four patients, though none had steatorrhea; there was a significant reduction in excretion of secondary bile acids; neutral sterol degradation rates were not affected by the drug. Slopes of plasma cholesterol-specific activity time curves did not change. These results fail to support the suggestion that neomycin acts as a bile acid precipitant. The finding of increased fecal neutral steroid excretion is consistent with decreased cholesterol absorption, but also with increased cholesterol absorption, but also with increased cholesterol synthesis (secondary to release of negative feedback control), with increased flux of cholesterol from tissues, or with a combination of all three actions.